2015
DOI: 10.1002/jmri.24940
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of readout segmented echo planar imaging (EPI) and EPI with reduced field‐of‐VIew diffusion‐weighted imaging at 3t in patients with breast cancer

Abstract: In breast cancer, rFOV EPI provided significantly higher image quality, lesion conspicuity, and SNR than rs-EPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
2
25
1
1
Order By: Relevance
“…They reported a prominent decrease in whole‐kidney ADCs caused by IOCM. Similar results were observed in this study by expending a novel RESOLVE DWI, which has shown previously better ability in improvement of image quality than traditional ss‐EPI . Benefited from these individual features, signal difference between the kidney cortex and medulla can be well monitored: we found that ADC CO was rarely affected by the administration of any CM, while the ADC in medullary kidney was significantly changed by means of administration of different CMs.…”
Section: Discussionsupporting
confidence: 88%
“…They reported a prominent decrease in whole‐kidney ADCs caused by IOCM. Similar results were observed in this study by expending a novel RESOLVE DWI, which has shown previously better ability in improvement of image quality than traditional ss‐EPI . Benefited from these individual features, signal difference between the kidney cortex and medulla can be well monitored: we found that ADC CO was rarely affected by the administration of any CM, while the ADC in medullary kidney was significantly changed by means of administration of different CMs.…”
Section: Discussionsupporting
confidence: 88%
“…Inevitable distortions and artifacts in the fFOV DWI sequence are caused by slow traversal through the k ‐space line and narrow bandwidth. However, the rFOV DWI sequence exhibited no RF crosstalk among slices and accelerates the traversal through the k ‐space line along the phase‐encoding direction with a shortened readout, thus improving the IQ with fewer distortions and artifacts . These superiorities of the rFOV DWI sequence compared with the fFOV DWI sequence, in terms of higher resolution with excellent fat suppression and diminished susceptibility artifacts, more clearly reveal the details of rectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…This approach must either suppress the surrounding regions (outer volume suppression [OVS]) or excite only the target region (inner volume excitation [IVI]). The latter approach (IVI) has found application to breast cancer in a range of studies using a two‐dimensional (2D) spectral‐spatial excitation . rFOV is highly applicable for breast lesion assessment where delineation of lesion borders and heterogeneity separate from the surrounding fibroglandular or adipose tissue can be challenging with conventional EPI, Figure .…”
Section: Emerging Techniquesmentioning
confidence: 99%
“…The latter approach (IVI) has found application to breast cancer in a range of studies using a two-dimensional (2D) spectral-spatial excitation. [87][88][89][90] rFOV is highly applicable for breast lesion assessment where delineation of lesion borders and heterogeneity separate from the surrounding fibroglandular or adipose tissue can be challenging with conventional EPI, Figure 10. Initial studies have shown both quantitative differences (i.e., lower ADC values) and qualitative differences (i.e., better defined border features and regional variations) between rFOV and conventional methods.…”
Section: Emerging Techniquesmentioning
confidence: 99%